2022
DOI: 10.1007/s40747-022-00807-5
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid fuzzy AHP–TOPSIS approach to prioritizing solutions for inverse reinforcement learning

Abstract: Reinforcement learning (RL) techniques nurture building up solutions for sequential decision-making problems under uncertainty and ambiguity. RL has agents with a reward function that interacts with a dynamic environment to find out an optimal policy. There are problems associated with RL like the reward function should be specified in advance, design difficulties and unable to handle large complex problems, etc. This led to the development of inverse reinforcement learning (IRL). IRL also suffers from many pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Montalbo et al [ 24 ] recommended the Multi-Fused Residual CNN (MFuRe-CNN) for analyzing endoscopic images of GI illnesses using the Kvasir dataset in 2022. Gibson et al reported a neural network design for segmentation of eight organs [ 25 ]. The pancreas, digestive system, "esophagus, stomach, and duodenum," are all necessary for endoscopic referral to the biliary and pancreatic processes.…”
Section: Related Workmentioning
confidence: 99%
“…Montalbo et al [ 24 ] recommended the Multi-Fused Residual CNN (MFuRe-CNN) for analyzing endoscopic images of GI illnesses using the Kvasir dataset in 2022. Gibson et al reported a neural network design for segmentation of eight organs [ 25 ]. The pancreas, digestive system, "esophagus, stomach, and duodenum," are all necessary for endoscopic referral to the biliary and pancreatic processes.…”
Section: Related Workmentioning
confidence: 99%
“…The Specific Energy Consumption (SEC) of a RO desalination plant can be determined by local water demand, water quality, first year of operation, and energy source. A mathematical model can be created to optimize SEC, bearing in mind retentate pressure drop and membrane capacity demand ratio [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The choice of the energy source, e.g.…”
Section: ) Technical Feasibilitymentioning
confidence: 99%
“…By combining these two methods, decision makers can effectively assess and prioritize alternatives based on multiple criteria, considering both qualitative and quantitative factors. This approach has been applied in various domains, such as solid waste management [23] and supplier evaluation and selection [24].…”
Section: ) Social and Political Feasibilitymentioning
confidence: 99%
See 1 more Smart Citation